Identifying a consistent pattern of neural function in attention deficit hyperactivity disorder: a meta-analysis. Issue 4 (13th May 2013) - McCarthy, H.; Skokauskas, N.; Frodl, T.
Abstract : Background: The neurobiological underpinnings of attention deficit hyperactivity disorder (ADHD) are inconclusive. Activation abnormalities across brain regions in ADHD compared with healthy controls highlighted in task-based functional magnetic resonance imaging (fMRI) studies are heterogeneous. To identify a consistent pattern of neural dysfunction in ADHD, a meta-analysis of fMRI studies using Go/no-go, Stop and N-back tasks was undertaken. Method: Several databases were searched using the key words: 'ADHD and fMRI' and 'ADHD and fMRI task'. In all, 20 studies met inclusion criteria comprising 334 patients with ADHD and 372 healthy controls and were split into N-back, Stop task and Go/no-go case–control groups. Using Signed Differential Mapping each batch was meta-analysed individually and meta-regression analyses were used to examine the effects of exposure to methylphenidate (MPH), length of MPH wash-out period, ADHD subtype, age and intelligence quotient (IQ) differences upon neural dysfunction in ADHD. Results: Across all tasks less activity in frontal lobe regions compared with controls was detected. Less exposure to treatment and lengthier wash-out times resulted in less left medial frontal cortex activation in N-back and Go/no-go studies. Higher percentage of combined-type ADHD resulted in less superior and inferior frontal gyrus activation. Different IQ scores between groups were linked to reduced right caudate activity in ADHD. Conclusions: Consistent frontal deficits imply homogeneous cognitive strategies involved in ADHD behavioural control. Our findings suggest a link between fMRI results and the potentially normalizing effect of treatment and signify a need for segregated examination and contrast of differences in sample characteristics in future studies.